NILAI RELATIF JABATAN MENGGUNAKAN METODE POIN SYSTEM DI CV SBM - Dian Puspitasari; Tri Hardjanti Nugrahaningsih (BISMA: Jurnal Bisnis dan Manajemen, 2021)
This study aims to determine the relative value of the job level at CV SBM as the basis for determining wages or salaries. Data analysis was performed based on cases that occurred in CV SBM. The key informants were all employees holding a minimum position as a cashier at CV SBM to obtain information concerning job descriptions and job specifications. Meanwhile, the director provided information related to factors and sub-factors for the compensation, including the weights. Data were analyzed at the job evaluation stage, from job analysis to grouping positions according to job class. The study results found that the relative job value for director positions was 1000 points, the supervisor was 761 points, the head of inventory was 599 points, the head of finance was 560 points, the cashier was 384 points, and the counter staff was 369. Wage levels were divided into three classes, i.e., the first class consisted of the cashier, counter staff, and head of finance; the second class consisted of the head of inventory and supervisor; and the third class consisted of the director. Based on these findings, the remuneration will be arranged according to the class of position. Keywords: analytical hierarchical processes, job evaluation, job relative value, wage/salary-based point system